Human Metapneumovirus, Australia, 2001–2004 - Theo P. Sloots (Emerging Infectious Diseases, 2006)
We examined 10,025 respiratory samples collected for 4 years (2001–2004) and found a 7.1% average annual incidence of human metapneumovirus. The epidemic peak of infection was late winter to spring, and genotyping showed a change in predominant viral genotype in 3 of the 4 years.